EZH2 Promotes T Follicular Helper Cell Differentiation Through Enhancing STAT3 Phosphorylation in Patients With Primary Sjögren’s Syndrome - He, Chengmei; Yang, Yanlei; Chen, Zhilei; Liu, Suying; Lyu, Taibiao; Zeng, Liuting; Wang, Li; Li, Yongzhe; Wang, Mu; Chen, Hua; Zhang, Fengchun (Frontiers in Immunology, 2022)
Objectives: Enhancer of zeste homolog 2 (EZH2) is an epigenetic regulator and plays an important role in immune system development and autoimmune diseases. This study aimed to characterize the role of EZH2 in the pathogenesis of primary Sjögren’s syndrome (pSS). Methods: We analyzed two transcriptomic datasets of peripheral blood mononuclear cells (PBMCs) from pSS patients and controls. We measured EZH2 expressions in CD4+ T cells, CD8+ T cells and CD19+ B cells from pSS patients and healthy controls, and correlation of EZH2 expression with clinical parameters. We also examined the activation, proliferation, T cell differentiation of CD4+ T cells using EZH2 inhibitor GSK126, EZH2 siRNA and EZH2-epxressing vector. We further examined STAT3 signaling pathway after EZH2 inhibition and detected Tfh differentiation in EZH2-overexpressed CD4+ T cells with STAT3 knocked down. Results: EZH2 was upregulated in both datasets. EZH2 expression was higher in pSS CD4+ and CD8+ T cells, and EZH2 expression in pSS CD4+ T cells was positively correlated with IgG, IgA, ESR, RF and peripheral Tfh population. EZH2 inhibition and silencing EZH2 suppressed activation, proliferation and Tfh differentiation in pSS CD4+ T cells. Furthermore, overexpressing EZH2 promoted activation, proliferation and Tfh differentiation in pSS CD4+ T cells. EZH2 inhibition attenuated STAT3 phosphorylation in CD4+ T cells. STAT3 knockdown aborted EZH2-promoted Tfh differentiation. Conclusions: EZH2 expression was abnormally elevated in pSS CD4+ T cells, which facilitated Tfh differentiation of CD4+ T cells through enhancing STAT3 phosphorylation. EZH2 might be implicated in pSS pathogenesis and was a potential therapeutic target of pSS.